Premature birth: complexities and difficulties in building the mother–child relationship. (20th October 2017) - Ionio, Chiara; Lista, Gianluca; Mascheroni, Eleonora; Olivari, Maria Giulia; Confalonieri, Emanuela; Mastrangelo, Massimo; Brazzoduro, Valeria; Balestriero, Maria Antonella; Banfi, Annamaria; Bonanomi, Andrea; Bova, Stefania; Castoldi, Francesca; et al.
Abstract: Aim: This paper aims to investigate if the dyadic interactive behaviours were influenced by parental stress and feelings both in preterm and full-term mother–child dyads. Methods: 45 mothers (age = 35.29 ± 5.38) and fathers (age = 36.77 ± 6.89) of preterm infants (GA = 30.25 ± 2.95; BW = 1288.02 ± 488.76), and 36 mothers (age = 32.60 ± 4.56) and fathers (age = 35.54 ± 5.16) of full-term (GA = 39.88 ± 1.38; BW = 3156.39 ± 493.81) were involved. Parents filled out the Impact of Event Scale Revised (IES-R), Profile of Mood States (POMS) and Parenting Stress Index Short Form (PSI-SF) and interactive behaviours (Global Rating Scale) was videotaped after 3 months. Results: Mothers of preterm children showed higher level of Intrusiveness (Mpreterm  = 4.07 ± .74, Mfullterm  = 4.39 ± .51, t = 2.22, p = .029) and Remoteness (Mpreterm  = 4.45 ± .83, Mfullterm  = 4.79 ± .34, t = 2.51, p = .015) than mothers of term children. In preterm mothers' lower levels of Sensitivity, higher levels of Intrusiveness, Remoteness and Depression are associated with the presence of negative feelings and parental stress in both parents. Moreover, higher children Distress is associated to parental negative feelings, paternal stress and post-traumatic symptoms. A higher score of parental negative feelings and parental stress predicted lower scores in Global RatingScale dimensions. Conclusions: Our results underline that preterm birth could be a risk factor for the co-construction of interactive exchanges between mother and premature baby. This study could help practitioners to better consider parental roles and to carry out specific supportive interventions for both parents and children.